Tacca plantaginea (Hence) Drenth (Taccaceae) - A new angiospermic record for Bangladesh - Hassan, MA; Uddin, Mohammad Zashim (Bangladesh Journal of Plant Taxonomy, 2007)
Not available. Key words: Tacca plantaginea, New record, Bangladesh DOI: 10.3329/bjpt.v14i1.525 Bangladesh J. Plant Taxon. 14(1): 71-73, 2007 (June)